Influence of customer satisfaction on service quality and trust relationship in Malaysian rural tourism / Zahir Osman and Ilham Sentosa - Sentosa, Ilham (Faculty of Business Management, 2013)
The main purpose of this study is to develop a mediating effect understanding of customer satisfaction on service quality and trust relationship in Malaysia rural tourism. The model was developed and later tested by adopting the partial Least Square (PLS) procedure on data collected from a survey that yielded 295 usable questionnaires. The findings showed that service quality enhances satisfaction in Malaysia rural tourism. It was also revealed that satisfaction partially mediates the relationship between service quality and trust. In future more research needs to be carried out to explore the role of satisfaction in Malaysia rural tourism industry. It is important to do the study utilizing experimental design by capturing longitudinal data in Malaysia rural tourism industry using robust measures. The findings imply that the relationship between satisfaction and profitability may reside in satisfaction’s influence on trust, and that satisfaction plays a crucial function within the Malaysia rural tourism industry. This research is one of the first known attempts to use PLS to test a mediation effect.